Prospects for the Development of Free Economic Zones in Uzbekistan - Kuzieva Nargiza Ramazanovna (International Journal on Integrated Education, 2022)
The article outlines current issues on active development of the production of competitive and export-oriented modern industrial products of the regions of the country, attraction of foreign and local investments to create modern production facilities to ensure the production of competitive products with high added value and in demand on foreign markets, taking into account the deep processing of mineral raw materials and agricultural resources. At the same time, the essence of the organization of free economic zones for creating favorable conditions for their functioning and an effective mechanism for applying tax and customs privileges in these regions are analyzed.